Inflammasome: A Double-Edged Sword in Liver Diseases - Luan, Jingyun; Ju, Dianwen (Frontiers in Immunology, 2018)
Inflammasomes have emerged as critical innate sensors of host immune that defense against pathogen infection, metabolism syndrome, cellular stress and cancer metastasis in the liver. The assembly of inflammasome activates caspase-1, which promotes the maturation of interleukin-1β (IL-1β) and interleukin-18 (IL-18), and initiates pyroptotic cell death (pyroptosis). IL-18 exerts pleiotropic effects on hepatic NK cells, priming FasL-mediated cytotoxicity, and interferon-γ (IFN-γ)-dependent responses to prevent the development of liver diseases. However, considerable attention has been attracted to the pathogenic role of inflammasomes in various acute and chronic liver diseases, including viral hepatitis, nanoparticle-induced liver injury, alcoholic and non-alcoholic steatohepatitis. In this review, we summarize the latest advances on the physiological and pathological roles of inflammasomes for further development of inflammasome-based therapeutic strategies for human liver diseases.